2007
DOI: 10.1038/sj.cdd.4402085
|View full text |Cite
|
Sign up to set email alerts
|

RIP1, a kinase on the crossroads of a cell's decision to live or die

Abstract: Binding of inflammatory cytokines to their receptors, stimulation of pathogen recognition receptors by pathogen-associated molecular patterns, and DNA damage induce specific signalling events. A cell that is exposed to these signals can respond by activation of NF-jB, mitogen-activated protein kinases and interferon regulatory factors, resulting in the upregulation of antiapoptotic proteins and of several cytokines. The consequent survival may or may not be accompanied by an inflammatory response. Alternativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
420
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 431 publications
(436 citation statements)
references
References 86 publications
14
420
2
Order By: Relevance
“…IRAK-1 and IRAK-4 mediate TLR/IL-1R signaling, and their counterparts in TNF-R signaling are RIP1 and most likely RIP4 [105]. However, RIP1 seems to be a more universal player, which can also take part in TLR signaling and many other receptor specific signaling pathways to NF-kB [106]. TLR/IL-1R as well as TNF-R signaling does not depend on the catalytic activity of the above-mentioned kinases, although they are functionally active.…”
Section: Discussionmentioning
confidence: 99%
“…IRAK-1 and IRAK-4 mediate TLR/IL-1R signaling, and their counterparts in TNF-R signaling are RIP1 and most likely RIP4 [105]. However, RIP1 seems to be a more universal player, which can also take part in TLR signaling and many other receptor specific signaling pathways to NF-kB [106]. TLR/IL-1R as well as TNF-R signaling does not depend on the catalytic activity of the above-mentioned kinases, although they are functionally active.…”
Section: Discussionmentioning
confidence: 99%
“…While receptorinteracting protein 1 (RIP1) can participate in signaling for both apoptosis and necrosis [3,4], recent studies by us and by others have shown that RIP3 is essential for TNF-induced necroptosis [5][6][7] and has no role in TNFinduced apoptosis [6,7]. Classification of TNF-induced cell death in a number of cell lines, such as L929 and murine embryonic fibroblasts (MEFs), has been made based on morphological and/or biochemical parameters [2,[7][8][9][10].…”
Section: Dear Editormentioning
confidence: 99%
“…[7][8][9][10] Interestingly, RIP1 has also been implicated in the apoptotic process triggered by several death receptors. 11 This suggests that apoptosis and necrosis, initially defined as mutually exclusive cell death processes, might paradoxically share several regulatory components.…”
mentioning
confidence: 99%